Особливості резистентності капілярного кровотоку в студентів при оклюзійній пробі - Станішевська, Тетяна; Горна, Оксана; Горбань, Дар’я; Stanishevska, Tatiana; Gorna, Oksana; Horban, Darya (Східноєвропейський національний університет імені Лесі Українки, 2016)
Експериментальне дослідження включало вивчення функціонального стану капілярного кровотоку за допомогою методу лазерної допплерівської флоуметрії (ЛДФ) у юнаків та дівчат. Аналіз стану кровотоку дав підставу виявити ознаки його зміни при оклюзійній пробі. Установлено, що рівень резистентності на оклю- зійну пробу залежав від типу мікроциркуляції крові. The experimental research consisted of the study of blood microcirculation functional state by means of Laser Doppler flowmetry (LDF) method. It helped to evaluate the state of tissue blood-circulation and to reveal individual-typological peculiarities of blood microcirculation. 192 adolescent boys and girls, the students of Melitopol Bohdan Khmelnytskyi State Pedagogical University, aged 17-22, were examined. The obtained results showed that at most of students high-amplitude LDF was registered. According to LDF three types of blood microcirculation were revealed: normoemic, hyperemic, and hypoemic types. Resistance people' whom studied capillary blood flow on occlusion test depended on various types of blood microcirculation. Resistance students’ capillary blood flow on occlusion test was the greatest at students with hypoemics’ type of blood microcirculation, at students with hyperemics’ and normoemics’ types of blood microcirculation was much lower.
Peculiarities of Resistance Students’ Capillary Blood Flow on Occlusion Test.
Keywords: капілярний кровоток; оклюзійна проба; резистентність капілярного кровотоку; параметр мікроциркуляції; лазерна допплерівська флуометрія (ЛДФ); capillary blood flow; occlusion test; resistance capillary blood flow; option of microcirculation; Laser Doppler flowmetry (LDF)